Life Cycle Assessment for the Organocatalytic Synthesis of Glycerol Carbonate Methacrylate. Issue 12 (30th May 2019) - Büttner, Hendrik; Kohrt, Christina; Wulf, Christoph; Schäffner, Benjamin; Groenke, Karsten; Hu, Yuya; Kruse, Daniela; Werner, Thomas
Abstract: Bifunctional ammonium and phosphonium salts have been identified as potential organocatalysts for the synthesis of glycerol carbonate methacrylate (GCMA). Three of these catalysts showed high efficiency and allowed the conversion of glycidyl methacrylate with CO2 to the desired product in >99 % conversion and selectivity. Subsequently, immobilized analogues of selected catalysts were prepared and tested. A phenol‐substituted phosphonium salt on a silica support proved to be a promising candidate in recycling experiments. The same catalyst was used in 12 consecutive runs, resulting in GCMA yields of up to 88 %. Furthermore, a life cycle assessment was conducted for the synthesis of GCMA starting from epichlorohydrin (EPH) and methacrylic acid (MAA). For the functional unit of 1 kg GCMA, 15 wt % was attributed to the incorporation of CO2, which led to a reduction of the global warming potential of 3 % for the overall process. Abstract : Finding the greenest route : Bifunctional ammonium and phosphonium salts are identified as potential organocatalysts for the synthesis of glycerol carbonate methacrylate (GCMA), with three of them giving the desired product in >99 % conversion and selectivity. A life cycle assessment is conducted to identify a potential reduction of the global warming potential of 3 % for the overall process.